+0  
 
0
299
1
avatar

3(2-x)=5(2x-7)+2

Guest Jul 11, 2017
edited by Guest  Jul 11, 2017
 #1
avatar+2248 
+2

In this equation, our goal is to isolate the unknown, x. Let's see how we would go about doing that

 

\(3(2-x)=5(2x-7)+2\) This is the original equation. Distribute the 3 and the 5 into the given parentheses.
\(6-3x=10x-35+2\) Combine -35+2.
\(6-3x=10x-33\) Add 33 to both sides,
\(39-3x=10x\) Add 3x to both sides.
\(39=13x\) Divide by 13 to isolate x. 
\(3=x\)  
   

 

There ya go!

TheXSquaredFactor  Jul 11, 2017

26 Online Users

avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.